Determinan Kemiskinan di Provinsi Nusa Tenggara Timur - Muhammad Wijdan Nabil; Reikha Habibah Yusfi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to examine the impact of the Labor Force Participation Rate (LFPR), the Human Development Index (HDI), and economic growth on poverty in East Nusa Tenggara (NTT) from 2014 to 2024. The study employs panel data combining cross-sectional data from 22 regencies/cities in NTT with an 11-year time series, resulting in 242 observation units. Panel data regression analysis was conducted using the Fixed Effects Model (FEM), determined to be the most appropriate model. The research findings indicate that the LFPR has a significant negative impact on poverty, suggesting that increased workforce participation contributes to poverty reduction, albeit to a relatively small extent. The HDI also has a significant negative impact on poverty, demonstrating that improving workforce quality—through education, health, and a decent standard of living—plays a crucial role in alleviating poverty. Meanwhile, economic growth shows a negative but insignificant impact on poverty, indicating that financial progress in NTT has not been fully inclusive and has failed to reach the poor population equitably. These results highlight the importance of improving workforce quality, creating productive employment opportunities, and fostering more inclusive economic development as strategies to reduce poverty in NTT.